Anggaran Berbasis Kinerja, Sistem Pelaporan Keuangan Dan Pengendalian Akuntansi Terhadap Akuntabilitas Kinerja - Rizka Saptarinur; Siti Rofingatun; Rama Soyan Arung Lamba (Jurnal Akuntansi dan Keuangan Daerah, 2022)
This study aims to determine the effect of performance-based budgeting, financial reporting systems, accounting controls, and performance accountability of government agencies on BPMP Papua Province either simultaneously or partially. This type of research is quantitative descriptive. The population in this study were all employees who were part of the SAKIP team and were involved in the financial process, preparing program performance drafts, budgets, and performance reporting and evaluation as well as several staff of 70 employees who worked at BPMP Papua. This research is a survey research where 70 samples are saturated samples and use a questionnaire as a data collection tool. The analysis tool used multiple regression analysis with the help of the SPSS Version 25 program. The results showed that partially performance-based budgeting and accounting control variables had a significant positive effect on government agency performance accountability, while the financial reporting system variable had no significant effect on government agency performance accountability. Simultaneously performance-based budgeting, financial reporting systems and accounting controls have a significant positive effect on government agency performance accountability at BPMP Papua Province.